(m,λ)-Berezin Transform on the Weighted Bergman Spaces over the Polydisk - Ran Li; Yufeng Lu (Journal of Function Spaces)
We prove that every bounded linear operator on weighted Bergman space over the polydisk can be approximated by Toeplitz operators under some conditions. The main tool here is the so-called (m,λ)-Berezin transform. In particular, our results generalized the results of K. Nam and D. C. Zheng to the case of operators acting on Aλ2(Dn).